Curriculum Management in The Character Forming of Students - Ardianto; Usman, Muhammad Umair Khan; Gunawan; Sholihah, Maidatus (Andragogi: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the curriculum development and preparation mechanism used at Madrasah Ibtidaiyah Al Busyro and explain how the curriculum at Madrasah Ibtidaiyah Al Busyro shapes the students' character. The data sources for this research are the principal, vice-principal for curriculum, vice-principal for student affairs, teachers, and students. Data collection techniques used observation notes, interview notes, and documentation. The data processing technique uses several stages: data collection, data reduction, data presentation, and conclusion. The results of this study are 1) Curriculum planning at Madrasah Al Busyro Palang Tuban, which is planned by setting goals to be achieved; 2) Curriculum management in shaping the character of students at Madrasah Ibtidaiyah Al Busyro Palang Tuban by implementing Islamic and exemplary religious programs obtained from the teacher council; 3) Evaluation of the curriculum in the formation of the character of students at MI Al Busyro is carried out twice a year as a whole and for the character education itself contained in the curriculum, evaluations are carried out quarterly or every three months. The results obtained are: The curriculum used at MI Al Busyro Palang Tuban is a combination of the Curriculum of the Ministry of Religion with the Unique Curriculum of the Al Busyro Institution in which there is a flagship program of MI Al Busyro, which aims to shape the character of students. Efforts to build student character at MI Al Busyro Palang Tuban with habituation, mentoring, and continuous example are considered successful and successful.